Pengaruh Citra Destinasi Dan Promosi Digital Terhadap Minat Berkunjung Wisatawan Pada Objek Wisata Di Kecamatan Pangururan Kabupaten Samosir - Regina Patrisia Harianja; Natalia E.T. Sihombing; Kepler Sinaga (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
The purpose of this study is to determine the influence of destination image and digital promotion strategies on tourists' interest in visiting tourist attractions in Pangururan District, Samosir Regency. Destination image refers to tourists' perspectives regarding the attractions, facilities, and uniqueness of the place. On the other hand, digital promotion is a marketing method carried out through online platforms to attract tourists' attention. These two factors are very important in increasing tourist interest in visiting. The method used in this study is quantitative by conducting a survey. Questionnaires were distributed to 100 respondents taken by accidental sampling technique. To analyze the data, instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing were carried out. The results of the partial test (t-test) showed that destination image had a t-value of 7.957 which was more than 1.66 and a significance of 0.000 which was less than 0.05. In addition, digital promotion showed a t-value of 7.650 which was also more than 1.66 and a significance of 0.000 which was still below 0.05. In the simultaneous test (F test), the calculated F value was 21.461, which was greater than 3.09 with a significance of 0.000, which was less than 0.05.